Antibacterial mechanism of Malaysian Carey clay against food-borne Staphylococcus aureus - Azmi, Nur Naqiyah; Mahyudin, Nor Ainy; Wan Omar, Wan Hasyera; Abdullah, Abdul Halim; Ismail, Roslan; Ishak, Che Fauziah; Sharples, Gary J. (Taylor and Francis, 2024)
Depending on their chemical structure and geochemistry, clay minerals can display potent antibacterial properties against a range of bacterial pathogens. Malaysian Carey clay was evaluated for its antibacterial activity against food-borne Staphylococcus aureus ATCC 13565 strains. The minimum inhibitory concentration (MIC) and minimum bactericidal activity (MBC) of both Carey clay leachates and suspension were 125 mg/mL and 250 mg/mL, respectively. Time-kill assay revealed that 2x MIC and 4x MIC Carey clay in both leachate and suspension forms resulted in complete killing of S. aureus. Antibacterial mechanism was investigated through imaging of bacterial morphology using TEM and determination of reactive oxygen species (ROS) using NBT assay. Imaging of bacterial morphology using TEM showed abnormalities, including disrupted cell walls following exposure to Carey clay, and the antibacterial activity was associated with generation of ROS. Our study suggests that Carey clay displays promising functionality as a natural antibacterial agent in the food industry.